2016
DOI: 10.1152/ajpendo.00330.2015
|View full text |Cite
|
Sign up to set email alerts
|

AP2-NR4A3 transgenic mice display reduced serum epinephrine because of increased catecholamine catabolism in adipose tissue

Abstract: -The NR4A orphan nuclear receptors function as early response genes to numerous stimuli. Our laboratory has previously demonstrated that overexpression of NR4A3 (NOR-1, MINOR) in 3T3-L1 adipocytes enhances insulinstimulated glucose uptake. To assess the in vivo effect of NR4A3 on adipocytes, we generated transgenic mice with NR4A3 overexpression driven by the adipocyte fatty acid-binding protein (AP2) promoter (AP2-NR4A3 mice). We hypothesized that AP2-NR4A3 mice would display enhanced glucose tolerance and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Adipocyte lipolysis was performed as previously described. 38,39 Epidydimal white adipose tissue (eWAT) was excised from each mouse and minced into 1 mm pieces in digest medium (Dulbecco's Modified Eagles Medium [DMEM], 1 g/L glucose, 4% fatty acid-free bovine serum albumin [BSA]). Tissue was digested in 0.3% collagenase I for 1 h at 37°C with gentle agitation.…”
Section: Ex Vivo Adipocyte Lipolysismentioning
confidence: 99%
“…Adipocyte lipolysis was performed as previously described. 38,39 Epidydimal white adipose tissue (eWAT) was excised from each mouse and minced into 1 mm pieces in digest medium (Dulbecco's Modified Eagles Medium [DMEM], 1 g/L glucose, 4% fatty acid-free bovine serum albumin [BSA]). Tissue was digested in 0.3% collagenase I for 1 h at 37°C with gentle agitation.…”
Section: Ex Vivo Adipocyte Lipolysismentioning
confidence: 99%
“…We obtained eight mutant lines generated by the ZMP (Table 1) (16). The eight ZMP mutants were selected as candidate regulators of adiposity based on published experimental evidence or by genomewide association studies (28)(29)(30)(31)(32)(33)(34)(35). Heterozygous carriers from the ZMP mutants were intercrossed, the offspring was raised to 30 dpf, and then Nile Red was used to visualize AT levels (Fig.…”
Section: Identification Of Nrp2b As a Novel Gene Implicated In Zebrafmentioning
confidence: 99%
“…They improve tolerance in peripheral T cells in response to chronic antigenic stimuli and also prevent improper B-cell responses to self-antigens [ 26 ]. Nr4a3 is a transcription factor involved in multiple functions in vascular biology [ 27 , 28 ], inflammation [ 29 , 30 ], glycolipid metabolism [ 31 ] and tumor immunity [ 32 ]. This study found that the gene Nr4a3 was significantly increased following PI3K/AKT or PKC/ERK pathways activation during MCs activation.…”
Section: Discussionmentioning
confidence: 99%